jQuery Recipes - Harwanid, B.M. (Apress, 2012)
jQuery a rich bundle of JavaScript libraries that helps users apply dynamic functionality to web pages with great ease. jQuery provides several powerful features, including the ability to access a part of a web page, modify the content on fly, add animation, apply AJAX, and more. This book uses a problem-solution approach to understanding the wide features provided by this open source project. Beginning by using selectors to apply effects to paragraphs and lists, we learn how to set the layouts of a web page. After that, we cover techniques involved in event handling, followed by performing validations to different form elements. Applying visual effects, navigations, AJAX and many more facets of jQuery are also explained in the form of recipes. The coding used in all the recipes is completely explained with screen shots at each step. If you know a bit of HTML, CSS and jQuery, then this is the book for you, as it is covers most of the problems a person faces while working with jQuery.